Scope of the Legal Stability Contracts of the Mining Sector: An Approach to the Additional Investments Not Foreseen in the Stability Contract - Taboada Pérez, Fabio Arturo (2014)
During the 90s, the Peruvian government implemented a series of economic and tax to promote investment in the country. This article, after almost two decades and with the assumption of the changes that have arisen, will make a brief review of the background to the enactment of Law No. 30230 with regard to new investments not provided for in the Legal Stability Contracts. From ment, will show how the Law N ° 30230 institutionalizes a misinterpretation of the rules governing legal stability contracts. Then, we will discuss the reasons why the current regulation is not an appropriate tool to promote investment.Finally, we introduce the synthesis of this article through the conclusions.